Adecuación del transporte para el cuidado y rehabilitación de los monos aulladores afectados por la trata ilegal en Antioquia (2019)
Antioquia is the second region of Colombia where wild animals are most trafficked, according to the statistics of (Chávez, 2005) to this department the majority of the species arrive because the market is of easy access for the commercialization. The howler monkeys are the most trafficked and most violated by the way they are captured, of every 10 animals that are trafficked, 2 or 3 arrive to the market and so far have been found around 70 homes in each municipality, which have as pets howler monkeys. At the Santa Fe Zoo in Medellin, the majority of these species arrive for rehabilitation process that culminates in the recovery and the subsequent return to the natural habitat. Of the processes that are done in the rehabilitation of this species transport is one of the most important phases because it is the step to the definitive release of the animal, where the process is closed successfully and where there are variables of stress that are not solved with dispositive substitutes that have not been designed for the needs of these wild species. The current transport process is carried out in conventional containers for dogs that are not adapted to the dimensions or activities for this type of animal. The project proposes a solution for the transport of this species, from the centers of rehabilitation to the points of release, focused on the reduction of variables that generate stress in the monkey during the transfer, considering the manipulation by the caretaker and the Interaction of the group of monkeys during the transport period